Help others—be happy? The effect of altruistic behavior on happiness across cultures - Weiss-Sidi, Merav; Riemer, Hila (Frontiers in Psychology, 2023)
Research has established that altruistic behavior increases happiness. We examined this phenomenon across cultures, differentiating between individualistic and collectivist cultures. We propose that cultural variations in the notion of altruism lead to different effects of helping on the helper’s happiness. For individualists, altruism is linked to self-interest (“impure” altruism), and helping others results in increased happiness for the helper. For collectivists, altruism is focused on the recipient (“pure” altruism), and helping others is less likely to enhance the helper’s happiness. Four studies support our predictions. Study 1 measured the dispositions toward altruism among people with various cultural orientations. Consistent with our predictions, the findings showed that individualism (collectivism) was positively associated with tendencies reflecting more “impure” (“pure”) altruism. Two experimental studies then examined the moderating role of cultural orientation on the effect of spending money on oneself versus others (Study 2) or of doing a kind action (making tea for oneself versus others; Study 3). Both experimental studies demonstrated that altruistic behavior had a positive effect on happiness for individualists but not for collectivists. Finally, Study 4, which utilized data from the World Values Survey to examine the altruism–happiness link in various countries, displayed a stronger link between altruistic behavior and happiness in individualistic (vs. collectivist) cultures. Altogether, this research sheds light on cultural differences in the display of altruism, revealing different motivations for and consequences of altruistic behaviors.